2019
DOI: 10.17221/240/2019-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strip rotary tillage with subsoiling on soil enzyme activity, soil fertility, and wheat yield

Abstract: Inappropriate tillage and soil compaction threaten farmland sustainability in the Huang-Huai-Hai Plains of China. We aimed to explore the impact of plowing tillage, rotary tillage, strip rotary tillage, and strip rotary tillage coupled to a two-year subsoiling interval (STS) on soil quality at various soil depths and on wheat yield. Soil bulk density was substantially lower in the 30–45 cm depth under STS than under any other treatment, resulting in lower soil penetration resistance. Highest soil particle macr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…The improvement in the physical and chemical properties of the soil also could promote the development of crop roots (Guan et al, 2015a;He et al, 2019c). However, the increase in the bulk density was not favorable for the growth and development of wheat roots.…”
Section: Factors That Influence the Wue Of Winter Wheatmentioning
confidence: 99%
“…The improvement in the physical and chemical properties of the soil also could promote the development of crop roots (Guan et al, 2015a;He et al, 2019c). However, the increase in the bulk density was not favorable for the growth and development of wheat roots.…”
Section: Factors That Influence the Wue Of Winter Wheatmentioning
confidence: 99%
“…Many studies have found that the planting density of wheat is negatively correlated with the lodging resistance index; stems are gradually refined, and the length of the basal internodes increases [12]. The overall length of the stems reduces, and thus, the mechanical strength of the stems decreases [13]. Studies have shown that the planting density of winter wheat is closely related to leaf senescence and grain weight.…”
Section: Introductionmentioning
confidence: 99%
“…Cd is one of the most toxic heavy metal elements that harmful to the growth of plants and human health [1]. As a component of soil, the activity of enzyme can sensitively reflect the direction and intensity of biochemical reaction in soil [2]. The distribution of heavy metal ions in soil will affect soil enzyme activity, and it is feasible to detect soil heavy metal contamination with soil enzyme activity [3].…”
Section: Introductionmentioning
confidence: 99%